Antibody-Mediated Rejection and Sponge Effect in a Redo Lung Transplant Recipient - Ashwini Arjuna; Michael T. Olson; Sofya Tokman; Rajat Walia; Thalachallour Mohanakumar; A. Samad Hashimi; Michael A. Smith; Ross M. Bremner; Ashraf Omar (Case Reports in Transplantation)
Long-term survival after lung transplant remains severely limited by chronic lung allograft dysfunction. Antibody-mediated rejection of lung transplant allografts is usually caused by donor-specific antibodies (DSAs) directed toward donor human leukocyte antigens (HLAs). Typically, patients with antibody-mediated rejection have significantly higher circulating DSAs and increased mean fluorescence intensity than those without antibody-mediated rejection. However, some patients with antibody-mediated rejection have low mean fluorescence intensities, partly due to the “sponge effect” related to DSAs binding to HLA molecules within the lung. Herein, we report the case of an 18-year-old, female lung transplant recipient who required retransplantation and developed circulating DSAs directed toward the first allograft but detected in circulation only after retransplantation. The present case draws attention to a rare finding of sponge effect in a patient with antibody-mediated rejection leading to allograft failure.